Analisis Perawatan dan Penanganan Pada Trafo Distribusi 20KV di PT Krakatau Tirta Industri (Water Solution) - Achmad Dhyta Maulana; Mohammad Fatkhurrokhman (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
The power transformer is the main equipment in the electric power distribution system. The power transformer functions to distribute power by increasing the voltage from the generator into the transmission line. Therefore, maintenance and handling of disturbances in the 20 kV distribution transformer at PT Krakatau Tirta Industri which is held by PT Krakatau Industrial (Persero) uses the power quality method. The maintenance method and handling of disturbances in the 20 kv distribution transformer at PT Krakatau Tirta Industri which is held by PT Krakatau Industrial (Persero) uses the power quality method, which uses a mega ohm meter (megger meter) and to maintain power reliability and ETAP 12.6.0 application to measure voltage frequency, voltage stability, voltage harmonics and voltage drop. The results of the analysis in the maintenance of the 20 kv distribution transformer at PT Krakatau Tirta Industri with measurements that have been analyzed for insulation resistance with a Mega Ohm Meter (Megger tester) 500/1000 V, there is only one transformer whose coil is leaking, namely transformer number 7 which is in the table in 10 samples taken. When the transformer is damaged, PT Krakatau Tirta Industri immediately replaces it with a new transformer or replaces it with a car transformer (semi-permanent). Keywords: Maintenance, Distribution, Power, Water, Solution.